Método empírico para estimar la densidad básica en muestras pequeñas de madera - Valencia Manzo, Salvado; Vargas Hernández, Jesús (Instituto de Ecología, A.C., 2016)
An empirical method to calculate the volume of small samples of wood obtained with an increment borer, for the purpose of estimating specific gravity, was evaluated. The empirical method was compared with other methods commonly used: the water displacement method and the maximum moisture method. The mean values, standard deviation, specific gravity minimum and maximum obtained with the empirical method w ere significantly correlated with those values obtained with the other two methods. This indicates that the empirical method is a reliable option, as well as being faster and simpler, for estimating the specific gravity of small samples of regularly shaped wood.